AVALIAÇÃO DOS PROCEDIMENTOS PARA CONSERVAÇÃO E RESTAURAÇÃO DE EDIFICAÇÕES HISTÓRICAS - Cardoso, Ione Almeida Brigido (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This work presents the proposal of analysis of procedures for conservation and restoration of historic buildings, considering the efficiency and primacy of preserving, to the maximum, the original characteristics of such buildings. There are many historical conservation and restoration actions that do not take into account the multiplicity of materials used in its construction, in addition to the historical time in which the buildings were erected, which may lead to an architectural decharacterization of these properties and to reduce the performance of the buildings. It is in this context that the evaluation of procedures for the conservation and restoration of historic buildings gains relevance. thus, the overall objetive of this work plan is to study how the decharacterization of the architectural style of buildings and the degradation of their architectura can be avoided by avaluating the procedures for conservation and restoration of historic building in order to compare them with interventions success stories in similar contexts. It is necessary to take into account the social and economic context in which these buildings are inserted as well as the closest built environment, mapping the uses given to those buildings over the years and their possible architectural and structural decharacterizations.